Biosafety in the dental environment and prevalence of COVID-19 in Dentists in the state of Paraíba (Research, Society and Development, 2021)
The aim of this study was to evaluate the prevalence of dentists in the state of Paraíba affected by the new Coronavirus and their knowledge about biosafety standards to control the spread of the virus in the dental environment. The study was quantitative, analytical and descriptive, developed through the application of an electronic questionnaire for dentists in the state of Paraíba. Data were processed using the SPSS statistical program, version 21.0. and associations between variables were performed using the Chi-square test (95% CI). A total of 641 dentists participated in the survey, most of them female (65.2%), aged between 20 and 30 years (55.1%), working in the interior of the state (58.2%) and working in private dental clinic (43.3%); 27.8% of respondents said they did have the disease COVID-19 and 44.2% had mild symptoms; 98.4% said they have knowledge about the spread of the virus in the dental environment, the majority (77.7%) attended patients during the time of the COVID-19 outbreak and 41.8% reported feeling safe in providing care . Male professionals were the most infected and those who progressed more to the most severe symptoms of the disease, as well as those over 40 years old (p≤0.005). It is concluded that the prevalence of dental surgeons contaminated by COVID-19 is low and the professionals demonstrated knowledge regarding the biosafety protocols adopted to contain the spread of the disease in the dental environment.